If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4 + w)(5w + -8) = 0 Reorder the terms: (4 + w)(-8 + 5w) = 0 Multiply (4 + w) * (-8 + 5w) (4(-8 + 5w) + w(-8 + 5w)) = 0 ((-8 * 4 + 5w * 4) + w(-8 + 5w)) = 0 ((-32 + 20w) + w(-8 + 5w)) = 0 (-32 + 20w + (-8 * w + 5w * w)) = 0 (-32 + 20w + (-8w + 5w2)) = 0 Combine like terms: 20w + -8w = 12w (-32 + 12w + 5w2) = 0 Solving -32 + 12w + 5w2 = 0 Solving for variable 'w'. Factor a trinomial. (-4 + -1w)(8 + -5w) = 0Subproblem 1
Set the factor '(-4 + -1w)' equal to zero and attempt to solve: Simplifying -4 + -1w = 0 Solving -4 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1w = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1w = 0 + 4 -1w = 0 + 4 Combine like terms: 0 + 4 = 4 -1w = 4 Divide each side by '-1'. w = -4 Simplifying w = -4Subproblem 2
Set the factor '(8 + -5w)' equal to zero and attempt to solve: Simplifying 8 + -5w = 0 Solving 8 + -5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -5w = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -5w = 0 + -8 -5w = 0 + -8 Combine like terms: 0 + -8 = -8 -5w = -8 Divide each side by '-5'. w = 1.6 Simplifying w = 1.6Solution
w = {-4, 1.6}
| 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 | | (2z+5c-3a)-(6a+2c-4z)= | | -3(x+4)+13=-2x-11 | | (y-z-b)-(b+y+z)= | | (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 |